Inspiring Relationships: Indigenization Plan 2013-2014 - Camosun College (Author); Michel Corrine (Author) (2013)
From the Introduction: "The Indigenization Plan is a response to the opportunities and challenges that are arising alongside changing social, political, cultural, economic, relational, and educational realities of Aboriginal people within and around Camosun College."